Accountability for Curriculum Implementation in Ethiopian Primary Schools: Compact Relationship in Focus - Beyessa, Feyera; Kenea, Ambissa (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The study aims to investigate the compact or bureaucratic accountability relationship for curriculum implementation in primary schools. To achieve this objective, an exploratory case study type and a multiple case study (holistic) research design were employed. A purposeful sampling technique was used to select sites and respondents. Data were collected from both primary and secondary sources using face-to-face structured interviews and document analysis. Primary sources of data were three district or Worda Education Offices (WEOs) and three primary schools, from which three school principals, six teachers, and three WEOs’ curriculum and instructional experts were selected. The data were analyzed qualitatively using a thematic approach. The study reveals that the compact accountability relationship between the WEOs’ curriculum and instructional experts and the curriculum implementers was collapsed by key determinants such as weak capacity, poor monitoring progress, and politicization of the WEOs’ curriculum and instructional experts’ roles and responsibilities. This study also affirms that the accountability relationship was purposefully operational for easily achievable actions and politically attractive roles such as the improvement of students’ test scores by 10%, enhancing students’ enrollment, reducing students’ dropout rates, etc. that resulted in little implementation of curriculum components into classroom practices in a decentralized education system of primary schools.